Why Not Exactly? Revisiting the Alleged Arguments against the Artistic Sublime in Kant’s “Critique of the Aesthetic Power of Judgment” - Schubbach, Arno (Aesthetica Preprint, 2024)
The debate about whether, according to Kant, there can be an artistic sublime often fails to clarify the relationship of the “Analytic of the Sublime” to the “Analytic of the Beautiful” and to the short discourse on art of the Critique of the Power of Judgment (KU, § 43 to § 59). Therefore, three types of arguments are often conflated, which I would like to propose to distinguish as precisely as possible: 1. arguments that cast doubt on the possibility of aesthetic judgments with respect to works of art in general; 2. arguments that specifically put into question the experience of the beautiful in the arts; 3. arguments questioning the artistic sublime. Kant addresses the first two types of arguments in his ingenious argumentation of why we can experience works of art as beautiful at all. However, they are often readily understood as arguments against the possibility of an artistic sublime, which Kant, however, hardly discusses as such. By distinguishing these types of arguments, I want to pinpoint what exactly, according to Kant, stood in the way of the possibility of an artistic sublime – and to explore the possibility of artistic strategies to overcome these obstacles.